Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/2047487319871735
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of multiple cardiovascular risk factor control outside Western Europe: Findings from the International ChoLesterol management Practice Study

Abstract: Background Comprehensive control of multiple cardiovascular risk factors reduces cardiovascular risk but is difficult to achieve. Design A multinational, cross-sectional, observational study. Methods The International ChoLesterol management Practice Study (ICLPS) investigated achievement of European Society of Cardiology (ESC)/European Atherosclerosis Society (EAS) guideline low-density lipoprotein cholesterol (LDL-C) targets in patients receiving lipid-modifying therapy in countries outside Western Europe. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“… 4 – 8 In this context, several studies have reported that simultaneous achievement of cardiovascular risk prevention goals is poor. 9 , 10 , 17 , 18 To the best of our knowledge, the present study is the first to analyze the composite cardiovascular risk factors control in premature CAD patients, using former and recent stringent criteria. Our results highlight that less than 20% and 10% of premature CAD patients achieved non-strict or strict metabolic control, respectively.…”
Section: Discussionmentioning
confidence: 98%
“… 4 – 8 In this context, several studies have reported that simultaneous achievement of cardiovascular risk prevention goals is poor. 9 , 10 , 17 , 18 To the best of our knowledge, the present study is the first to analyze the composite cardiovascular risk factors control in premature CAD patients, using former and recent stringent criteria. Our results highlight that less than 20% and 10% of premature CAD patients achieved non-strict or strict metabolic control, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…In a large outpatient cohort in Italy, LDL-C levels were poorly controlled despite lipid-lowering therapy and lifestyle recommendations; none of the primary prevention patients with very high SCORE risks achieved the LDL-C target of <70 mg/dL (<1.8 mmol/L), and only 9% of high SCORE risk patients had an LDL-C of <100 mg/dL (2.6 mmol/L) [27]. In countries outside Western Europe, the proportion of high or very high CVD risk patients achieving treatment targets was 44% for LDL-C, 56% for blood pressure and 39% for diabetes, but only one-tenth of patients achieved simultaneous control of LDL-C, diabetes and blood pressure [25].…”
Section: Discussionmentioning
confidence: 99%
“…Especially low control rates were found for LDL-C (4.5%) and body weight parameters (15%). Numerous observational studies, including previous EUROASPIRE surveys, concluded that control of multiple cardiovascular risk factors is poor in clinical practice [20,[23][24][25][26][27], and it is even more difficult to achieve the targets in the primary prevention setting than in coronary patients [20]. In the primary care arm of EUROASPIRE IV, less than half (43%) of the treated patients reached the blood pressure target, one-third (33%) of patients achieved the LDL-C target of <2.5 mmol/L and less than two-thirds (59%) achieved the HbA1c target of <7.0%.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the study discussed in this editorial 9 was to evaluate the level of, and association between, multiple risk factor control in patients with dyslipidemia, diabetes and hypertension, in whom LDL-cholesterol, blood pressure and haemoglobin A1c (HbA1c) could be assessed. Its hypothesis was that patients with low control of one risk factor are less likely to achieve the control of others, in different countries and continents.…”
mentioning
confidence: 99%
“…The authors state that the control of risk factors did not differ markedly among countries and was identical to European countries with documented CAD. 9 However, the recently published paper of Euroaspire V latest results 7 referred only to patients with documented CAD and the ICLPS 9 included a heterogeneous population, without CAD and with CAD. Nevertheless, it confirms the need for better risk factor control, which will necessarily include strategies to support adherence to lifestyle modification and medication.…”
mentioning
confidence: 99%